The air borne disease becoming a blessing in disguise for the IT sectors in Bangladesh: a perspective on Ogroni Informatix Limited CRM - Rahman, Tasnim (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.